A dilatometric study of the phase transformations in 300 and 350 maraging steels during continuous heating rates - Carvalho,Leandro Gomes de (2013)
The influences of the chemical composition and heating rate have been studied in 300 and 350 maraging steels using dilatometry. For these tests, heating was carried out with heating rates of 1, 10 and 28 °C/s. The results have shown that the precipitation mechanism for both materials in the studied range is by lattice diffusion. Furthermore, Co and Ti contents influence strongly the precipitation. The lattice diffusion mechanism in the martensite reversion is influenced by Ni and Co contents and heating rate. For small heating rates ( ~1 °C/s) this mechanism prevails in the 300 maraging steel while for the 350 maraging steel has a minor importance. The mechanism of martensite reversion for 350 maraging steel in the studied range is mainly by shear mechanism. For higher heating rates (~28 ºC/s) the shear mechanism prevails in both maraging steels.